Compression therapies for the treatment of venous leg ulcers: study protocol for a process evaluation in a randomised controlled trial, VenUS 6 - Maartje Kletter; Jane Griffiths; Catherine Arundel; Jo Dumville; on behalf of the VenUS 6 Collaborators (Trials, 2023)
Abstract Background The VenUS 6 parallel-group randomised controlled trial (RCT) will compare the clinical and cost-effectiveness of compression wraps, two-layer compression bandage and evidence-based compression therapy, comprising of two-layers of hosiery or four-layer bandages, for healing time of venous leg ulcers. We will conduct an embedded process evaluation to evaluate the implementation of the trial and the various compression therapies and to gain a more in-depth understanding of trial participant and nursing staff views and experiences of these therapies. Methods This process evaluation will be a mixed-method study, embedded into a wider RCT. Qualitative data will be collected through semi-structured individual in-depth interviews with trial participants and staff members. Quantitative data will be collected using patient questionnaires and case report forms that are part of the main trial data collection process. Interview transcripts will be analysed using the Framework Analysis and interview data will be integrated with quantitative RCT data using the RE-AIM framework and the Pillar Integration Process. Discussion We describe the protocol for a process evaluation, designed to assess the implementation of the various venous leg ulcer compression therapies as evaluated in VenUS6, and the experiences of trial participants and nursing staff using these. This protocol provides one example of how an embedded mixed-method process evaluation can be conducted. Trial registration ISRCTN 67321719 ( https://doi.org/10.1186/ISRCTN67321719 ). Prospectively registered on 14 September 2020. Recruitment Infographic SWAT—MRC Hub for Trials Methodology Research SWAT repository #116. Registered on 13 April 2020. Retention Thank You Card SWAT—MRC Hub for Trials Methodology Research SWAT repository #119. Registered on 13 April 2020. Retention Newsletter SWAT—MRC Hub for Trials Methodology Research SWAT repository #28. Registered on 01 July 2007. Retention Pen SWAT—MRC Hub for Trials Methodology Research SWAT repository #92. Registered on 01 April 2019. Protocol version: V1.5, 26 May 2022.